Conversion of fly ash - an environmentally detrimental waste to zeolite beta (BEA) for commercial catalytic applications - Kasture, M. W.; Bokade, Vijay V.; Joshi, P. N. (Journal of the American Ceramic Society, 2005)
Zeolite beta (BEA) was synthesized hydrothermally using fly ash as a combined source of alumina and silica. The overall crystallization period required to obtain pure crystalline BEA zeolite was found to be slightly longer when fly ash was used. The physicochemical properties of BEA phases obtained using fly ash (FLBEA) and conventional source materials (CONBEA) were compared. The H/FLBEA catalyst has exhibited excellent catalytic performance in commercially important benzene isopropylation process. These results have demonstrated that converting fly ash into BEA zeolite not only alleviates the disposal problem but also turns an otherwise waste material into a marketable commodity.

Textural/structural, stability and morphological properties of mesostructured silicas (MCM-41 and MCM-48) prepared using different silica sources - Gaydhankar, T. R.; Taralkar, U. S.; Jha, Ratnesh Kumar; Joshi, P. N.; Kumar, R (Catalysis Communications, 2005)
A series of MCM-41 and MCM-48 samples have been synthesized under hydrothermal and static conditions using different silica sources (fumed silica, silica sot and ethyl silicate) and characterized by powder XRD, scanning electron microscopy and N-2 adsorption. The silica source reactivity trend observed was as: ethyl silicate > fumed silica > silica sot. However, the extent of contraction caused by calcination, magnitude of the wall thickness and stability were found to depend not only upon the type of silica source used but also on the type of structure formed. Noticeable morphological differences were observed in case of only MCM-41 when silica sources were varied. © 2005 Elsevier B.V. All rights reserved.

Hydrothermal synthesis of MCM-41 using differently manufactured amorphous dioxosilicon sources - Gaydhankar, T. R.; Samuel, V.; Joshi, P. N. (Materials Letters, 2006)
The influence of differently manufactured amorphous dioxosilicon sources such as fumed silica (FS), spray dried precipitated silica (PSI) and flash dried precipitated silica (PS,) on the course of structural development and properties of hydrothermally prepared siliceous MCM-41 phases have been investigated. Powder XRD, N-2 adsorption/desorption and scanning electron microscopy techniques were used for sample characterization. On the basis of results obtained from time dependent study on the progressive development of MCM-41 mesophases, the reactivity trend of dioxosilicon sources observed was as: FS > PS1 > PS2. MCM-41 synthesized using least expensive PS2 having less surface area has exhibited thicker pore walls but poor orderness, while MCM-41 prepared from expensive FS having high surface area has thinner pore walls and was well ordered. The extent of contraction caused by calcination, magnitude of the wall thickness and structural stability were found to be dependent on manufacturing process of dioxosilicon sources. The noticeable morphological differences were also observed by variations in the type of dioxosilicon sources used in the hydrothermal synthesis MCM-41 materials. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Characterization; dioxosilicon sources; Hydrothermal synthesis; MCM-41; porosity; Structural stability

Shape selective synthesis of long-chain linear alkyl benzene (LAB) with AIMCM-41/beta zeolite composite catalyst - Bordoloi, Ankur; Devassy, Biju M.; Niphadkar, P. S.; Joshi, P. N.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A-Chemical, 2006)
The liquid-phase alkylation of benzene with long-chain olefins such as 1-decene, 1-octene and 1-dodecene was carried out over AIMCM-41/Beta zeolite composite material as catalyst. The catalyst was prepared by seeding method and characterized by XRD, N-2 sorption, FTIR pyridine adsorption, NH3-TPD and SEM. Powder XRD of AlMCM-41/Beta zeolite composite material showed the co-existence of well-structured microporous and mesophase of AlMCM-41. The typical textural characteristics of micro- and meso-structured phases were observed in the composite material. The effect of temperature, reactant molar ratios and catalyst weight on 1-dodecene conversion and products selectivity was studied. The composite catalyst was found to be the highly selective towards the formation 2-dodecylbenzene. Under the reaction conditions of 120 degrees C, benzene/1-dodecene molar ratio 10 and time 2h, the catalyst gave 48% dodecene conversion with 76%, 2-dodecylbenzene selectivity. Significant improvement in catalytic activity has been achieved by composite material as compared to Al-MCM-41. Although zeolite beta and composite material gave similar conversion of dodecene, the composite material showed higher selectivity towards 2-dodecylbenzene, which could be due to higher diffusibility of 2-dodecylbenzene isomer in the composite material. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: AIMCM-41/beta zeolite composite; Alkylation; Benzene; long-chain olefins

Structural evolutions of hydrothermally prepared mesostructured MCM-48 silica using differently manufactured amorphous silica powders - Taralkar, U. S.; Jha, Ratnesh Kumar; Joshi, P. N. (Journal of Non-Crystalline Solids, 2007)
The hydrothermal synthesis of Si-MCM-48 mesoporous molecular sieves was carried out using a ternary SiO2:CTAOH:H2O System wherein differently manufactured amorphous silica powders such as fumed silica (FMDS), spray dried precipitated silica (SDPS) and flash dried precipitated silica (FDPS) were used as silica source materials. The changes in structural/textural properties were evaluated using powder XRD, N-2 adsorption-desorption and scanning electron microscopy techniques. Studies on the progressive development of MCM-48 mesophases revealed that, the reactivity of the silica source follow the trend: FMDS > SDPS > FDPS. MCM-48 synthesized using low cost FDPS has exhibited thicker pore walls but poorer orderness, while MCM-48 prepared from relatively expensive FMDS has thinner pore walls and more ordered structure. Moreover, the extent of contraction caused by calcinations, agglomerate size and structural stability were found to depend on the reactivity of the silica source used. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: long-range order; micelles; scanning electron microscopy; silica; silicates; sol-gels (xerogels); X-ray diffraction

Synthesis and characterization of value added catalysts zeolite beta using environmentally detrimental flyash - Kasture, M. W.; Bokade, Vijay V.; Joshi, P. N.; Kumar, R. (From Zeolites to Porous Mof Materials: the 40th Anniversary of International Zeolite Conference, Proceedings of the 15th International Zeolite Conference, 2007)
Fly ash is a major byproduct of Thermal power plant, which makes a lot of pollution to the environment due to its fineness. When a large amount of fly ash is dumped in the places near to power plants, it mixes in all segment of environment like water, air as well as soil. Though it can be utilized for different useful purposes, due to the lack of technical knowledge about how and proper motivation, no progress has been made in its utilization. It has been demonstrated that the fly ash can be used for making a value added catalyst zeolite beta by using simple and low cost process. In the present paper it is demonstrated that the fly ash can be used as a source of silica and alumina in the synthesis of value added catalyst zeolite beta. Moreover, the influence of different silica sources such as tetraethylortho silicate, silica sol and fumed silica on the physiochemical characteristics of well crystallized zeolite beta was also studied. The detailed characterization was carried out by using powder XRD, (27)Al and (29)Si MAS NMR, chemical analysis and low temperature nitrogen adsorption. Based on the data obtained from various systems containing different silica source, fumed silica is found to be most efficient source materials and showed superiority in the uniformity of aluminum distribution and possesses higher surface area.
15th International Zeolite Conference, Beijing, PEOPLES R CHINA, AUG 12-17, 2007

Influence of synthesis conditions on structural properties of MCM-48 - Taralkar, U. S.; Kasture, M. W.; Joshi, P. N. (Journal of Physics and Chemistry of Solids, 2008)
The influence of synthesis variables such as time, cetyltrimethyl ammonium hydroxide (CTAOH) concentration, water content, pH, temperature and silica source on the structural properties of Si-MCM-48 is investigated. Time-dependent studies on the progressive development of MCM-48 have indicated that synthesis time is a crucial parameter, which influences the unit cell parameter. The formation of different mesophases was observed when the concentration of CTAOH and pH of the initial gel were varied. The Si-29 MASNMR results showed that the (Q(2) +W-3)/Q(4) ratio decreases with the increase in synthesis temperature. On account of increase in W units at high-temperature synthesis run, Si-MCM-48 with highly polymerized silica walls with lower surface area was obtained when compared with Si-MCM-48 prepared at lower temperature. Such effect was not significant when Si-MCM-48 was synthesized at the same temperature but using silica sol as a source in place of fumed silica. (c) 2008 Elsevier Ltd. All rights reserved.

Synthesis, characterization and catalytic performance of Sn-MCM-48 in solvent-free Mukaiyama-type aldol condensation reactions - Taralkar, U. S.; Kalita, Pranjal; Kumar, Rajiv; Joshi, P. N. (Applied Catalysis A-General, 2009)
The influence of various synthesis variables on the physico-chemical properties of mesoporous stannosilicate molecular sieves with MCM-48 structure (Sn-MCM-48) has been investigated. Sn-MCM48 has been used as a new heterogeneous catalyst in solvent-free Mukaiyama-type aldol reactions. Invariably, the beta-hydroxy ester selectivity was found to be 100% irrespective of the conversion level. The product yield was found to increase, to reach a maximum (70%), and then to decrease with the increase in tin content. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Characterization; heterogeneous catalysis; Hydrothermal synthesis; Mesoporous molecular sieves; Mukaiyama-aldol condensation; Sn-MCM-48

Synthesis of N-methylaniline by aniline alkylation with methanol over Sn-MFI molecular sieve - Niphadkar, P. S.; Joshi, P. N.; Gurav, H. R.; Deshpande, Suvarna S.; Bokade, Vijay V. (Catalysis Letters, 2009)
Sn-MFI molecular sieves (Tin silicalite-1) with SiO(2)/SnO(2) molar ratio of 50-150 were synthesized and characterized. Elemental analysis, XRD and DRUV-vis confirmed that prepared samples were of MFI zeolite structure and Sn was incorporated in MFI framework. Vapor phase methylation of aniline over Sn-MFI was systematically studied and optimizations of process parameters were carried out. Sn-MFI (SiO(2)/SnO(2) = 50) was found to be optimum catalyst with 55% aniline conversion and 60% N-methylaniline selectivity. At lower space velocity (higher contact time) of 1 h(-1), aniline conversion was found to be increased to 71% with reduction in N-methylaniline selectivity to 39% and increased in N,N-dimethylaniline selectivity to 58%. The reaction follows first order kinetics with respect to aniline having activation energy of 7.3 kcal/mol.
Keywords: Aniline; Lewis acid; Methanol; N-methylaniline; Sn-MFI

Synthesis of Si-MCM-41 from ternary SiO2-CTAOH-H2O system via dry gel conversion route - Taralkar, U. S.; Niphadkar, P. S.; Joshi, P. N. (Journal of Sol-Gel Science and Technology, 2009)
Steam assisted dry gel conversion method was employed for the synthesis of Si-MCM-41 from ternary SiO2:CTAOH:H2O systems wherein fumed silica was used as a source of silica. The influence of synthesis time, molar ratios of CTAOH/SiO2 in dry gel and the water content at the bottom of autoclave on the quality and formation of mesophases has been investigated. Powder XRD, N-2 adsorption-desorption, TEM and hydrothermal stability test were the techniques used for sample characterization. Keeping molar ratio of CTAOH/SiO2 constant, shorter synthesis time, lower unit cell parameter and d spacing were observed when steam assisted dry gel conversion method was employed in place of conventional hydrothermal method. There exists an optimum lower limit for water content at the bottom of autoclave for reducing the synthesis period. Keeping synthesis temperature and CTAOH/SiO2 molar ratio fixed, Si-MCM-41 with improved hydrothermal stability was obtained by steam assisted dry gel conversion route.
Keywords: Dry gel conversion; powder diffraction; Si-MCM-41; Sol-gel growth; Structural stability; Textural properties

Transesterification of sunflower oil catalyzed by flyash-based solid catalysts - Kotwal, M. S.; Niphadkar, P. S.; Deshpande, Suvarna S.; Bokade, Vijay V.; Joshi, P. N. (Fuel, 2009)
Flyash-based base catalyst was used in the transesterification of sunflower oil with methanol to methyl esters in a heterogeneous manner. Catalyst preparation variables such as, the KNO(3) loading amount and calcination temperature were optimized. The catalysts were characterized by powder XRD. The catalyst prepared by loading of 5 wt.% KNO(3) on flyash followed by its calcination at 773 K has exhibited maximum oil conversion (87.5 wt.%). The influence of various reaction parameters such as % catalyst loading, methanol to oil molar ratio, reaction time, temperature, reusability of the catalyst on the catalytic activity was investigated. K(2)O derived from KNO(3) might be an essential component in the catalyst for its efficiency. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Flyash; heterogeneous catalyst; Methyl ester; Sunflower oil; transesterification

Influence of zeolitic structure on photoreduction property and hydrogen evolution reaction - Chatti, Ravikrishna V.; Dubey, Nidhi; Joshi, Meenal V.; Labhsetwar, Nitin K.; Joshi, P. N.; Rayalu, Sadhana S. (International Journal of Hydrogen Energy, 2010)
A new photocatalytic material developed by supporting TiO(2) in combination with transition metal ion like cobalt and heteropolyacid (HPA) on the surface is facilitating enhanced photoreduction of water and methyl orange Zeolites being a solid acid play an important role in the electron transfer reaction, facilitated by the Lewis acid sites in the form of aluminium ions In the present work, four different zeolite matrices namely, NaY zeolite, ultrastable zeolite Y, beta zeolite and titanium silicate-1 have been used for the synthesis of new photocatalytic materials These materials have been evaluated for water splitting by an initial screening procedure using methyl orange photoreduction The photocatalyst containing Na Y has emerged as a potential photocatalyst with hydrogen evolution rate of 2730 mu mol/h/g of TiO(2) Hydrogen evolution was not observed for the composite photocatalysts synthesized using the other zeolite matrices It has been observed that physicochemical properties like Si/Al ratio, acidity and basicity of the zeolite support have a tremendous influence on the photoreduction property of these zeolite matrices (C) 2010 Professor T Nejat Veziroglu Published by Elsevier Ltd All rights reserved
Keywords: H(2) evolution; Lewis acidity; Si/Al ratio; water splitting; Zeolite structure

Characterization of surface acid sites in tin-silicalite-1 (Sn-MFI) molecular sieve by X-ray photoelectron spectroscopy - Niphadkar, P. S.; Patil, K. R.; Joshi, P. N. (Microporous and Mesoporous Materials, 2011)
The nature, strength and density of surface acid sites in Sn-MFI molecular sieves with different Sn-content were characterized by N 1s high resolution photoelectron peak of chemisorbed pyridine in combination with pyridine-IR and TPAD. Two peaks emerged at 399.5 +/- 0.2 and 401.5 +/- 0.2 eV by deconvoluting composite N is peak were assigned to chemisorbed pyridine on weak and relatively strong Lewis acid sites, respectively. The relative percentage of strong Lewis acid sites was found to increase with the decrease of framework Sn content. A close agreement was observed between the ratios of weak Lewis acid sites to strong Lewis acid sites obtained from XPS and TPAD. (C) 2010 Elsevier Inc. All rights reserved.
Keywords: Lewis acidity; Pyridine chemisorption; SiO2/SnO2 molar ratio; Sn-MFI; XPS

Environmental potential applications of alkali metal exchanged zeolite x in carbon dioxide adsorption - Joshi, U. D.; Joshi, P. N.; Roh, H. S.; Yoon, W. L.; Shiralkar, V. P. (Research Journal of Chemistry and Environment, 2011)
The increasing atmospheric CO2 concentration, mainly caused by the Thermal Power Stations, Industrial sector and fossil fuel combustion, has led to consequences of global warming. Zeolitic adsorption processes is more promising, energy saving and viable method for CO2 removal in Comparison to other technologies. In order to examine the behavior and to establish the trends in carbon dioxide sorption, NaX zeolite (Si/Al = 1.15) and it's the modified forms with identical degree (55.5 +/- 2.5) of exchange by K+, Rb+ and Cs+ cations have been selected., The samples were characterized by powder XRD, Low temperature nitrogen adsorption/desorption measurements, chemical analysis and also for the intermediate electronegativity and the partial charges on the atoms using Sanderson's electronegativity equalization principle. The isotherms of carbon dioxide using these NaX, NaKX, NaRbX and NaCsX samples were measured at an interval of 30 K in the temperature range of 273 to 363 K up to 600 Torr. The uptake of CO2 was found to depend on both, the size of the nonframework cation and the temperature at which the isotherms were measured. The cations with lower charge density will have lower extent of electrostatic interaction with the sorbate molecules. Since CO2 has more linear quadrupole moment, it interacts mainly with the extra-framework cations and framework oxygen. The carbon dioxide sorption data satisfactorily represented by Langmuir and also analyzed for the chemical affinity. The Isosteric heat (q(st)) of NaX for the coverage of 20 molecules per unit cell is nearly equal to 26 kJ, mol(-1). The NaX and NaKX comparatively show a flat heat profile with the increasing amount sorbed than those of NaRbX and NaCsX indicating a balance between the strength of energetic heterogeneity of sorbate-sorbent interactions and sorbate-sorbate interactions.
Keywords: CO2 sorption; Ionic exchange; Isosteric heat; NaX zeolite; Theoretical models

Influence of Al3+ insertion in the stannosilicate MFI framework on the catalytic performance in vapor phase aniline N-methylation - Niphadkar, P. S.; Joshi, P. N.; Deshpande, Suvarna S.; Bokade, Vijay V. (Applied Catalysis A-General, 2011)
Silica-based Sn-MFI, Al-MFI and Al-Sn-MFI molecular sieves were synthesized by hydrothermal crystallization of gels having molar compositions SiO2:xSnO(2):yAl(2)O(3):0.23 (TPA)(2)O:35H(2)O, where x ranges from 1/0 to 1/200 and y from 1/0 to 1/400. Keeping molar Si/(Al + Sn) = 50, the amount of tin and aluminum in hydrogel was varied (Sn:Al molar ratios = 1:0, 1:0.33, 1:1, 1:3, 0:1) to investigate the synergy between Lewis and Bronsted acid sites in acid catalyzed aniline N-methylation reaction. Catalyst characterization was done by Powder X-ray diffraction, DRUV-vis spectroscopy, temperature programmed ammonia desorption (TPAD) and FTIR spectroscopy. An increase in the Al3+ insertion in Sn-MFI framework resulted in the increase in the stronger acid sites. Al-Sn-MFI showed higher aniline conversion than their monometallic counterparts. A sample having B/L ratio in between 0.67 and 0.91 was found to be optimum for maximizing the NMA yield, indicating the existence synergistic properties of Al-Sn-MFI. Upon process parameter optimization, the optimum sample M50 [Si/Al = 50.2, Si/Sn = 93.8, Si/(Al + Sn) = 43.2] showed the maximum aniline conversion (67%) and NMA selectivity (81%) at reaction temperature = 220 degrees C, weight hourly space velocity (WHSV) = 3 h(-1), molar ratio (aniline to methanol) = 1:8 and TOS = 4 h. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Al-Sn-MFI; Aniline; Bronsted and Lewis acid; Methanol; N-methylaniline

Copper modified waste fly ash as a promising catalyst for glycerol hydrogenolysis - Rode, C. V.; Mane, R. B.; Potdar, A. S.; Patil, P. B.; Niphadkar, P. S.; Joshi, P. N. (Catalysis Today, 2012)
Several catalyst formulations using waste fly ash along with Cu were prepared and characterised by XRD, BET and TEM. These catalysts were also evaluated for the first time for hydrogenolysis of glycerol to 1,2 propanediol (1,2-PDO) in a batch reactor under 52 bar H-2 pressure in the temperature range of 473-513 K conditions. The fly ash pretreated by alkali using the fusion method and impregnated with Cu showed higher activity and stability for glycerol hydrogenolysis. Due to pretreatment with alkali at high temperature, transformation of alpha-quartz to the tridymite phase of SiO2 occurred. More importantly, use of alkali either during the pretreatment or the Cu loading step resulted in a high dispersion on the surface which was responsible for higher glycerol conversion and 1,2-PDO selectivity. The effects of temperature, Cu loading and solvent on glycerol conversion and product selectivities were also studied in this work. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: 1; 2-Propanediol; Alkali fusion; Cu loading; Fly ash; Glycerol hydrogenolysis

Effect of preparation parameters of Cu catalysts on their physico-chemical properties and activities for glycerol hydrogenolysis - Mane, R. B.; Kondawar, S. E.; Niphadkar, P. S.; Joshi, P. N.; Patil, K. R.; Rode, C. V. (Catalysis Today, 2012)
Cu based catalysts were prepared by co-precipitation, alkali fusion followed by precipitation and direct solid state fusion methods. The changes in the phase formation, morphology, crystallite size, extent of aggregation, strength and nature of acid sites were observed due to variations in precipitating agents and also their order of addition. The catalyst prepared by co-precipitation using Na2CO3 showed the predominant presence of metallic Cu phase with a crystallite size of 5 nm, well segregated spherical morphology and highest acidity in the activated sample. These intrinsic properties contributed to achieve the highest glycerol conversion of 62% and 1,2-PDO selectivity of 88% in glycerol hydrogenolysis. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Co-precipitation; Cu catalysts; Glycerol hydrogenolysis; Physico-chemical properties; Solid state fusion

Thermal expansion properties of stannosilicate molecular sieve with MFI type structure - Niphadkar, P. S.; Bhange, Deu S.; Selvaraj, K.; Joshi, P. N. (Chemical Physics Letters, 2012)
An in situ high temperature X-ray diffraction study was carried out for investigating the thermal expansion properties of Si-MFI and SnSi-MFI molecular sieves. The thermal stability up to 973 K and a negative lattice thermal expansion in anisotropic manner was exhibited by both the phases in the temperature range of 373-973 K. The trend observed in contraction along the axes was as: a > c > b. The substitution of Sn4+ in MFI framework resulted in an expansion of unit cell volume and in an increase in the lattice thermal expansion coefficient in the temperature range 423-973 K. (C) 2012 Elsevier B. V. All rights reserved.

Bulk and surface structure characterization of nanoscopic silver doped lanthanum chromites - Desai, P. A.; Joshi, P. N.; Patil, K. R.; Athawale, Anjali A. (Applied Surface Science, 2013)
Crystalline state of lanthanum chromites with silver as a dopant has been studied by X-ray diffraction and transmission electron microscopy reveals microscopic properties of grain boundaries. X-ray photoelectron spectroscopy has been used to analyze surface states with atomic ratio of La, Cr, O and Ag as a dopant. LaCrO3 shows mixed valence states of chromium while the silver doped samples exhibit differences in chromium concentration with the oxidation of Cr3+ to Cr6+ in presence of chromium nitrate as a precursor salt. Trivalent stable state of chromium is observed for samples synthesized by chromic acetate as a precursor salt. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Energy dispersive analysis of X-rays; Microwave combustion synthesis; Perovskite nanostructures; transmission electron microscopy; X-ray diffraction; X-ray photoelectron spectroscopy

Crystallization kinetics of Sn-MFI molecular sieve formation by dry gel cross mark conversion method - Niphadkar, P. S.; Tangale, N. P.; Joshi, P. N.; Awate, S. V. (Microporous and Mesoporous Materials, 2013)
The conversion of amorphous stannosilicate dry gel into crystalline molecular sieve with MFI structure (Sn-MFI) was achieved by dry gel conversion (DGC) method at 413, 443 and 473 K. For comparison purpose, Sn-MFI molecular sieve with similar SiO2/SnO2 mole ratio was also obtained by hydrothermal crystallization route. Crystallization curves were established by conducting time dependant studies on progressive crystallization processes for both the systems. The values of activation energy of nucleation (E-n), activation energy of crystallization (E-c), and their pre-exponential factors (InA(n), InA(c) respectively) were calculated from Arrhenius plots. Compared to the hydrothermal method, shorter induction period was observed when DGC method was employed. Both the E-n (49.70 kJ/mol) and E-c (52.82 kJ/mol) for DGC method were found to be lower than that of the E-n (55.70 kJ/mop and E-c (60.23 kJ/mol) for hydrothermal method. The kinetics parameters viz. K and q were derived from kinetic expressions and DGC method showed higher value of K and lower value of q compared to hydrothermal crystallization method at identical temperature. Various DGC method parameters such as water content at the bottom of autoclave and SiO2/SnO2 mole ratio have shown the influence on the kinetics of crystallization of Sn-MFI. (C) 2013 Elsevier Inc. All rights reserved.
Keywords: Crystallization; DGC; kinetics; Nucleation; Sn-MFI

Effect of SnO2/Al2O3 ratio of Si-based MFI on its acidity and hydrophobicity: application in selective hydroxyalkylation of p-cresol - Garade, Ajit C.; Malwadkar, A. V.; Niphadkar, P. S.; Jha, Ratnesh Kumar; Joshi, P. N.; Rode, C. V. (Catalysis Communications, 2014)
Silica based MR type molecular sieves with various SnO2/Al2O3 ratios were synthesized from gels having molar compositions SiO2:xSnO(2):yAl(2)O(3):0.23(TPA)(2)O:35H(2)O where 0 <= x <= 0.02 and 0 <= y <= 0.01. Recyclable, Al-free Sn-MFI catalyst showed 31% conversion of formaldehyde with 100% selectivity to 2,2'-methylenebis(4-methylphenol) in hydroxyalkylation of p-cresol with formaldehyde on account of moderate acidity and higher hydrophobicity. (C) 2013 Elsevier B.A. All rights reserved.
Keywords: Al-27 MAS NMR; Hydroxyalkylation; Molecular sieves; p-Cresol; Stannosilicate

Esterification of levulinic acid to ethyl levulinate over bimodal micro-mesoporous H/BEA zeolite derivatives - Patil, C. R.; Niphadkar, P. S.; Bokade, Vijay V.; Joshi, P. N. (Catalysis Communications, 2014)
A series of bimodal micro-mesoporous H/BEA zeolite derivatives were prepared by the post-synthesis modification of H/BEA zeolite by NaOH (0.05 M-1.2 M) treatment Samples were characterized by powder XRD, low temperature nitrogen adsorption/desorption, temperature programmed desorption of ammonia and ICP. The mesopore formation was found to play a crucial role in liquid phase esterification of levulinic acid with ethanol. The enhanced catalytic activity of a bimodal micro-mesoporous H/BEA zeolite derivative (H/BEA(0.10)) prepared by treatment with 0.1M NaOH can be mainly attributed to the high mesoporosity coupled with better preserved crystallinity and acidic properties. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Esterification; ethyl levulinate; H/BEA zeolite; Mesoporosity; Post-synthesis modification

Synthesis, characterization and photocatalytic behavior of TiO2-SiO2 mesoporous composites in hydrogen generation from water splitting - Niphadkar, P. S.; Chitale, S. K.; Sonar, S. K.; Deshpande, Suvarna S.; Joshi, P. N.; Awate, S. V. (Journal of Materials Science, 2014)
TiO2-SiO2 mesoporous composite photocatalysts with different proportions (in wt%) of TiO2 and SiO2 (TiO2-SiO2 = 20:80, 40:60, 60:40, 80:20 and 100:0) were prepared by loading TiO2 on as-synthesized Si-MCM-41 using sol-gel method. The physicochemical properties of composites were investigated by powder X-ray diffraction, N-2 adsorption-desorption measurements, transmission electron microscopy and UV-Vis diffuse reflectance spectroscopy. It is revealed that the titanium species are dispersed as TiO2 having interaction with the surface of the support. Even at high TiO2 loading, the mesostructural feature of MCM-41 was found to be intact without pore blockages. The change in morphology of TiO2 particle was observed with increase in TiO2 loading which may be due to different environment for the growth of TiO2. The photocatalytic evaluation of composites was carried out in production of hydrogen by water splitting. Among the prepared samples, mesoporous composite containing 60 % TiO2 (MTi60) has shown the best results (0.08805 mmol of H-2/h/g of TiO2) compared to other composite photocatalysts. The catalytic performance of this sample was further enhanced (similar to 8 times) after loading 1 % Pt in water splitting (0.70161 mmol of H-2/h/g of TiO2). 1 % Pt loaded on pure TiO2 (MTi100) showed hydrogen evolution of the magnitude 0.26 mmol of H-2/h/g of TiO2. TiO2-SiO2 mesoporous composite photocatalyst showed much higher activity (similar to 1.9 times) than amorphous silica-embedded titania catalyst having same composition.

Synthesis of Sn-containing anatase (TiO2) by sol-gel method and their performance in catalytic water splitting under visible light as a function of tin content - Tangale, N. P.; Niphadkar, P. S.; Samuel, V.; Deshpande, Suvarna S.; Joshi, P. N.; Awate, S. V. (Materials Letters, 2016)
Sol-gel route was employed to prepare a series of Sn-containing anatase with different molar (Ti/Sn) ratios ranging from 49 to 1. Samples were characterized by powder XRD, UV-vis, XPS, SEM, EDAX, low temperature N-2 sorption technique and Raman Spectroscopy. Except anatase phase, no other crystalline phase was observed when Ti/Sn molar ratio was varied from 49 to 9 and for Sn free sample. However, further decrease in the ratio lead to the appearance of additional SnO2 phase whose peak intensities were increased with the increase in the tin content. Irrespective of tin content, all samples showed red-shift in UV-vis spectra. Moreover, samples showed Raman shift to higher vibration side from 143 cm(-1) to 147 cm(-1) indicating the doping of Sn2+ into TiO2. By virtue of low band gap, anatase crystallite size and an absence of XRD visible SnO2, ST (19) has shown maximum photocatalytic activity upon 1 wt% Pt loading. It has exhibited the highest rate (0.1264 mmole/g/h) for visible light induced hydrogen evolution by water splitting. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Semiconductors; Sn2+ doped titania; SnO2/TiO2; Sol-gel preparation; visible light; water splitting

Hierarchical K/LTL zeolite as solid base for aqueous phase hydrogenation of xylose to xylitol - Tangale N. P.; Niphadkar, P. S.; Joshi, P. N.; Dhepe, P. L. (Microporous and Mesoporous Materials, 2019)
Post-synthesis modification by alkali treatment was employed for the synthesis of hierarchical K/LTL zeolites with varying degree of mesoporosity. For the alkali treatment, the concentration of aqueous KOH solution was changed from 0.3 to 2.8 M keeping the quantity per gram of zeolite fixed. The influence of the alkali concentration on the chemical composition, powder XRD crystallinity, morphology, basicity, and the textural properties of resultant hierarchical zeolites was investigated. Variation in the concentration of KOH solution was found to control the degree of preferential desilication with the preserved structural fingerprint of K/LTL zeolite. As a result, the generation of mesoporosity was observed along with 1) the decrease in the Si/Al ratio and percentage relative crystallinity, and 2) an increase in BET surface area and mesopore volume. 27Al MAS-NMR results showed that all the aluminum atoms present in the tetrahedral coordination after alkali treatment, which provides an elegant approach for significantly increasing the basic sites in the hierarchical zeolites. As a heterogeneous catalyst, the hierarchical K/LTL zeolites demonstrated the improved performance in the hydrogenation of xylose to xylitol as compared to the parent K/LTL zeolite. The different process parameters were assessed in order to maximize the hydrogenation activity. Among all the hierarchical zeolites, the enhanced catalytic activity was shown by the hierarchical K/LTL prepared by using 1.5 M KOH solution when it is used along with the 3.5 wt% platinum loaded γ-Al2O3 catalyst. This optimum activity may be attributed to the higher surface area, accessible basic sites, nano-sized Pt on γ-Al2O3, and the development of substantial intracrystalline mesoporosity for the enhanced molecular diffusion of reactant to and from the hierarchical zeolite with better-preserved crystallinity.